Out-of-Hospital ICU Transfers to an Oncological Referral Center: Characteristics, Resource Utilization, and Patient Outcomes. (January 2019) - Gutierrez, Cristina; Cárdenas, Yenny R.; Bratcher, Kristie; Melancon, Judd; Myers, Jason; Campbell, Jeannee Y.; Feng, Lei; Price, Kristen J.; Nates, Joseph L.
Objective: To determine resource utilization and outcomes of out-of-hospital transfer patients admitted to the intensive care unit (ICU) of a cancer referral center. Design: Single-center cohort. Setting: A tertiary oncological center. Patients: Patients older than 18 years transferred to our ICU from an outside hospital between January 2013 and December 2015. Measurements and Main Results: A total of 2127 (90.3%) were emergency department (ED) ICU admissions and 228 (9.7%) out-of-hospital transfers. The ICU length of stay (LOS) was longer in the out-of-hospital transfers when compared to all other ED ICU admissions ( P = .001); however, ICU and hospital mortality were similar between both groups. The majority of patients were transferred for a higher level of care (77.2%); there was no difference in the amount of interventions performed, ICU LOS, and ICU mortality between nonhigher level-of-care and higher level-of-care patients. Factors associated with an ICU LOS ≥10days were a higher Sequential Organ Failure Assessment (SOFA) score, weekend admissions, presence of shock, need for mechanical ventilation, and acute kidney injury on admission or during ICU stay ( P < .008). The ICU mortality of transferred patients was 17.5% and associated risk factors were older age, higher SOFA score on admission, use of mechanical ventilation and vasopressors during ICU stay, and renal failure on admission ( P < .0001). Data related to the transfer such as LOS at the outside facility, time of transfer, delay in transfer, and longer distance traveled were not associated with increased LOS or mortality in our study. Conclusion: Organ failure severity on admission, and not transfer-related factors, continues to be the best predictor of outcomes of critically ill patients with cancer when transferred from other facilities to the ICU. Our data suggest that transferring critically ill patients with cancer to a specialized center does not lead to worse outcomes or increased resource utilization when compared to patients admitted from the ED.